CBCT and CAD-CAM technology to design a minimally invasive maxillary expander - Diego Sánchez-Riofrío (BMC Oral Health, 2020)
Abstract Background A large number of articles in recent years studying the effects of non-surgically assisted tooth- versus bone-borne maxillary expanders in growing patients have found no significant differences in mid-palatal suture disjunction or even dentoalveolar changes. This suggests the need for new criteria and better use of current technology to make more effective devices and enhance the benefits of conventional treatments. This article describes a titanium grade V computer-aided design/computer-aided manufacturing (CAD/CAM) maxillary expander supported by two miniscrews, along with a 3D printed surgical guide. Methods The first step was to obtain a digitized model of the patient’s upper maxilla. To simplify the process and ensure the placement of the device in a high-quality bone area, the patients’ digital dental cast was superimposed with a cone beam computed tomography (CBCT) scan. Improved resistance to expansion forces was secured through the use of 2 mm-wide miniscrews, long enough for bicortical anchorage. Placement site and direction were assessed individually in order to achieve primary stability. We chose a site between the second premolars and first molars, while the inclination followed the natural contour of the palate vault. A 3D-printed, polyamide surgical guide was designed to ensure the correct placement of the device with a manual straight driver. Results Favorable clinical results were presented with 3D images. We confirmed a mid-palatal suture parallel separation of 3.63 mm, along with a higher palatal volume, as well as increased intercanine and intermolar distance. Segmentation of the facial soft tissue showed an expansion of nasal airways and changes in nasal morphology. Conclusions Digital models, CBCT and CAD/CAM technology, are essential to accomplish the goals proposed in this article. Further studies are necessary to establish safer miniscrew placement sites and insertion angles so as to achieve greater in-treatment stability. Both the clinician and the patient can benefit from the use of current technology, creating new devices and updating traditional orthodontic procedures.